The Impact of Online Social Networks on Decision Support Systems - Antunes, Francisco (2015)
Previous research on this matter had already determined that many concepts are encompassed by both online social networking and decision support systems research. Due to the large number of concepts and using clustering techniques, we were able to determine four concept clusters, namely: the technical infrastructure, online communities, network analysis and knowledge management. Then, we intended to gain further knowledge on how those concepts influenced DSS related research and the contribution of each cluster to the support of the phases of decision-making process. We also wanted to perceive the interconnections among the concept clusters themselves, for which we used structural equation modeling techniques. The obtained results evidence that not only online social networks are being used as a technical infrastructure to support the three decision making phases and to support knowledge management and online communities, but also that the other clusters only regard the intelligence phase of the decision process.